Can the monocyte/HDL ratio predict ear effusion in adenoid vegetation patients? - Elif Kaya Çelik; Fatih Öner (The Egyptian Journal of Otolaryngology)
Abstract Background Since monocytes secrete cytokines, high monocyte counts may indicate subclinical inflammation. HDL-C, a significant component of total cholesterol, may reduce inflammation. Objectives This study investigated whether the monocyte/HDL ratio (MHR) could be an independent predictive marker in patients with adenoid vegetation, both with and without otitis media with effusion (OME). Methods This cross-sectional study included patients diagnosed with adenoid vegetation, with or without OME, who underwent surgery. The groups consisted of patients who underwent adenoidectomy alone for adenoid vegetation and those who underwent adenoidectomy + ventilation tube for adenoid vegetation with OME (Group 2). Monocyte counts, HDL-C levels, and MHR values were calculated for both groups. Results The mean age of Group 1 was 6.95 ± 2.77 years, while Group 2 had a mean age of 6.61 ± 2.98 years. No significant difference was found in monocyte count or percentage between the groups. The HDL-C ratios were lower in Group 2, which OME accompanied, and the difference between the groups was significant (p: 0.027). The MHR was not significantly different between Groups 1 and 2, with values of 10.47 (4.22–29.23) and 12.29 (5.43–99.6), respectively. Conclusion Reduced MHR ratios may indicate elevated inflammatory levels in the body and may be linked to certain medical conditions. However, we found no significant difference in the parameters’ ability to predict OME in children with adenoid vegetation. Therefore, a simple, low-cost marker to predict middle ear effusion in children is needed.